Analisis Pemasaran Jagung Di Kecamatan Ulubongka Kabupaten Tojo Una-Una - Rahmah I. Lihawa (Universitas Tadulako, 2019)
This research aims to determine the marketing channels, marketing margin, marketing efficiency and prices part. This research was conducted at Ulubongka district with sample of villages at Borneang and Bongka Makmur village. The locations were selected purposively, because these areas have the harvested area and the highest production at Ulubongka district. Each village samples was taken each 22 farmers. Numbers of merchants sampled were 5 people traders and 2 wholesalers. The analysis model used marketing margin analysis, marketing efficiency and prices part. The result showed two corn marketing channel at Ulubongka district. The smallest total marketing margin obtained on the marketing channel II. Corn marketing efficiency obtained on the marketing channel II was smaller than marketing channels I and part of the price obtained channel II greater than marketing channels I. The corn marketing channels at Ulubongka district efficient is a marketing channel II.